Pengaruh Financial Technology, Literasi Keuangan Dan Gender Terhadap Perilaku Keuangan Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Nadiah Putri Salsabila; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study was conducted to examine the effect of the variables Financial Technology, Financial Literacy, and Gender on Financial Behavior in Students of the Faculty of Economics and Business, Islamic University of Malang . The population in this study is 598. The sampling technique used is purposive sampling and obtained as many as 86 students. The data analyzed using multiple linear regression. The results showed that Financial Technology no significant effect on Financial Behavior. Financial Literacy significant effect on Financial Behavior. Gender significant effect on Financial Behavior. Keywords: Financial Technology, Financial Literacy, Gender